1991
DOI: 10.2135/cropsci1991.0011183x003100020026x
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation Effects on Grain Fill, Stalk Rot, and Lodging of Grain Sorghum

Abstract: Yield response to defoliation in grain sorghum [Sorghum bicolor (L.) Moench] can be influenced by time and intensity of leaf removal. Limited information is available for defoliation ✕ environment interactions and the defoliation response of yield‐related traits, stalk rot, and basal stalk lodging. This study was conducted to examine the effect of time and extent of defoliation on hybrid grain sorghum in three eastern Nebraska environments in relation to yield components, duration and rate of grain filling, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Genetically, male sterile plants showed a twofold increase in assimilate storage in the stems, indicating that removal of a grain sink increases stem sugar (Fortmeier and Schubert, 1995). Leaf defoliation during anthesis promoted lodging, suggesting that it may be due to depletion of carbohydrates from the stem (Rajewski and Francis, 1991). Conversely, each plant sink events (plant height, flowering time and tillering) may increase sugar production potential in nonstress environments (Murray et al, 2008).…”
Section: Solute Accumulation and Storage Sugarmentioning
confidence: 99%
“…Genetically, male sterile plants showed a twofold increase in assimilate storage in the stems, indicating that removal of a grain sink increases stem sugar (Fortmeier and Schubert, 1995). Leaf defoliation during anthesis promoted lodging, suggesting that it may be due to depletion of carbohydrates from the stem (Rajewski and Francis, 1991). Conversely, each plant sink events (plant height, flowering time and tillering) may increase sugar production potential in nonstress environments (Murray et al, 2008).…”
Section: Solute Accumulation and Storage Sugarmentioning
confidence: 99%
“…Fourteen genotypic groups derived from the Tx642  Tx7000 recombinant inbred line (RIL) population carrying a combination stg QTL were evaluated under three environments in four replications. High levels of sugar in the stem were also reported to reduce the incidence of stalk and root rot diseases caused by M. phaseolina (Clark and Miller, 1980;Hiremath and Parvatikar, 1985;Rajewski and Francis, 1991). Genotypes carrying either stg1 or stg3, or their combination stg1+3 expressed high levels of resistance to M. phaseolina.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if we had chosen to defoliate our experimental plants only at onset of flowering, or later, we would have erroneously concluded that seed size showed a greater response to defoliation. Agricultural studies have also shown that delaying the time of stress relative to floral and fruit development decreases the negative effect on fruit and seed number but increasingly depresses seed weight (e.g., Sharrow, 1990;Rajewski and Francis, 1991).…”
Section: Discussionmentioning
confidence: 99%